A Atuação do BNDES no Desenvolvimento Econômico Brasileiro:1952 - 2002 - Lima, Alexandre de Santana (2007)
In 1952, The BNDE Banco Nacional de Desenvolvimento Econômico was created, with the objectives of providing long term financing and guiding the industrialization and economic development in Brazil. The creation of BNDES is a consequence of an accelerated industrialization process; need to reduce under development and the external dependency, all of which have derived from the primary-exporter characteristic of the Brazilian economy. For over fifty years, the Bank has gone through many different economic and development policies that have been conducted by the Brazilian Government. During its first thirty years, BNDE was tightly tied to infrastructure foundation and heavy industries, supported by public and domestic private capital investments. During the last decade of the 20th century, with the changes in the State s role, from agent to enabler of development, the Bank has new attributions, as the main figure in the privatization process and economic development through private companies, domestic or international, having the State as the main tutor. This paper s objective is to study BNDE s evolution throughout its first fifty years of existence, focusing on the period between 1990 and 2002